Leadership Effectiveness, Organizational Commitment and Job Satisfaction Towards Employee Performance at PT. Hilon Sumatera - Sijabat, Lastri Putri Br; Syafii, M. (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to test and analyze the influence of leadership effectiveness, organizational commitment and job satisfaction on employee performance at PT. Hilon Sumatera. Data collection was carried out through questionnaires, interviews and documentation. The population of employees in the production department of PT. Hilon Sumatera, as many as 55 people with a sample of 55 people taken using saturated sampling techniques or census. The analysis techniques used in this study are validity and reliability tests, multiple linear regression analysis and hypothesis testing. Data analysis in this study used SPSS version 25. The results of this study formulated that the multiple regression equation is Y = 5.516 + 0.319X1 + 0.356X2 + 0.245X3 meaning that the t test shows that leadership effectiveness has a positive and significant effect on employee performance at PT. Hilon Sumatera with a value of t count (3.719)> t table (1.675) with a significant level of 0.000 <0.05 so that the decision H0 is rejected and H1 is accepted. This means that the variable of leadership effectiveness has a positive and significant effect on employee performance at PT. Hilon Sumatera. The t-value (2.809) > t-table (1.675) with a significant level of 0.007 <0.05 so that the decision is taken H0 is rejected and H1 is accepted. This means that the variable of organizational commitment has a positive and significant effect on employee performance at PT. Hilon Sumatera. The t-value (2.608) > t-table (1.675) with a significant level of 0.012 <0.05 so that the decision is taken H0 is rejected and H1 is accepted. This means that the variable of job satisfaction has a positive and significant effect on employee performance at PT. Hilon Sumatera. The value of the determinant coefficient (R Square) of 0.378 means that employee performance can be explained by leadership effectiveness, organizational commitment and job satisfaction by 37.8%, while the remaining 62.2% can be explained by other factors such as work stress, workload, work discipline that were not examined in this study.